Periodic acid-Schiff and alcian blue immunohistochemistry to detect mucin in mucinous breast carcinoma (Medical Journal of Indonesia, 2020)
BACKGROUND Detection of mucins has been shown to correlate with several clinicopathological characteristics in patients. Currently, periodic acid-Schiff (PAS) and alcian blue staining methods are the histochemistry staining techniques that are frequently used to detect mucin. This study was aimed to evaluate PAS and alcian blue staining in differentiating mucin characteristics between invasive carcinoma of no special type (ICNST) with mucinous degeneration and mucinous carcinoma. METHODS This cross-sectional study of 33 cases included biopsies of mucinous breast carcinoma and ICNST with mucin degeneration that were histologically verified using hematoxylin and eosin (H&E) staining. The PAS and alcian blue staining were conducted in the Laboratory of Histochemistry, Department of Anatomical Pathology, Cipto Mangunkusumo Hospital. Data were recorded using SPSS software, version 21 (IBM Corp, USA). RESULTS There were 17 cases of ICNST with mucinous degeneration and 16 cases of mucinous carcinoma with age varied from 27 to 75 years. PAS had sensitivity of 87.5% and specificity of 41.2%. Alcian blue had sensitivity of 43.8% and specificity of 82.4%. CONCLUSIONS PAS staining method is better than the alcian blue staining method in distinguishing between ICNST with mucinous degeneration and mucinous carcinoma. In the limited setting laboratory, PAS staining alone can be considered to detect mucin.